Olympic Sport Organisations in Times of Crisis and Change Guide for Strategic Management and Good Governance - Schallhorn, Christiana (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
Modern management is strategic and purpose-driven and has often been neglected in sports organizations. Here, for the first time, in close cooperation with eleven National Olympic Committees and the EOC EU Office of Sport, a guide to strategic management for sports organizations is presented, which also includes crisis and change management and increases crisis resilience. It is aimed at all those interested in (sports) management of NPOs and Olympic organizations in particular. It is a good read and includes many workshops, case studies, examples and best practice applications. The authors have been researching sports management, Olympic research and sports communication for years.